PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE SNOWBALL THROWING UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SDS PEMBANGUNAN BAGAN BATU - Nenti Hasintongan; Eddy Noviana; Mahmud Alpusari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research is based on the low learning outcomes of fourth grade science students in SDS Pembangunan Bagan Batu academic year 2016/2017. Initial data received by the researcher, from 25 students who reached the value of KKM only 7 students (28%) with an average of 56.8. This research is a classroom action research conducted collaboratively and participatively in collaboration with science teacher of class IV in SDS Pembangunan Bagan Batu. The instrument of this research consists of learning device used in this research based on Education Unit Level Curriculum (KTSP). Learning tools consist of syllabus, lesson plans, student worksheets and observation sheets. The result of research got the activity of teacher at first cycle of meeting I that is 58,33% with enough category, second cycle meeting to I that is 70,83% with good category. At siklu II meeting 1 that is 79,167% with good category and second meeting second cycle that is 91,67% with very good category. Then the percentage of first cycle activity of the first student is 54,167% with enough category, at the second meeting of cycle I that is 70,83% with good category. In the second cycle of meeting I is 83.33% with very good category, and the second meeting is 87.5% with very good category. As for the result of student learning that complete before held action only 7 student (28%) with average value 56,8. In the daily test I cycle I the number of completed students increased to 14 students or (56%) with an average score of 68.6. Furthermore, in II repetition cycle II increased again with the total number of students who complete as many as 23 students or (92%) with an average value of 84.2. The increase that occurred on student learning outcomes between the basic score of one cycle with the percentage of 20.77% and between the basic score of the second cycle with the percentage of 48.23%. This means that the classical value obtained by students has been above the established KKM.Keywords: Cooperative Learning Model Snowball Throwing, Learning Outcomes Ipa